Posterior Reversible Encephalopathy Syndrome and Reversible Cerebral Vasoconstriction Syndrome: Clinical and Radiological Considerations - Pilato, Fabio; Distefano, Marisa; Calandrelli, Rosalinda (Frontiers in Neurology, 2020)
Posterior reversible encephalopathy syndrome (PRES) and reversible cerebral vasoconstriction syndrome (RCVS) are relatively uncommon neurological disorders, but their detection has been increasing mainly due to clinical awareness and spreading of magnetic resonance imaging (MRI). Because these syndromes share some common clinical and radiologic features and occasionally occur in the same patient, misdiagnosis may occur. PRES is characterized by varied neurological symptoms including headache, impaired visual acuity or visual field deficit, confusion, disorders of consciousness, seizures, and motor deficits often associated to peculiar neuroradiological pattern even if uncommon localization and ischemic or hemorrhagic lesions were described. RCVS is a group of diseases typically associated with severe headaches and reversible segmental vasoconstriction of cerebral arteries, often complicated by ischemic or hemorrhagic stroke. Pathophysiological basis of PRES and RCVS are still debated but, because they share some risk factors and clinical features, a possible common origin has been supposed. Clinical course is usually self-limiting, but prognosis may fluctuate from complete recovery to death due to complications of ischemic stroke or intracranial hemorrhage. Neuroradiological techniques such as digital angiography and MRI are helpful in the diagnostic pathway and a possible prognostic role of MRI has been suggested. This review will serve to summarize clinical, neuroradiological features and controversies underlying both syndromes that may mislead the diagnostic pathway and their possible relationship with pathophysiology, clinical course, and prognosis.